An inquiry on the on-the-job training experiences of accounting interns - Fuentes, Erica Angela; Javier, Kizzie Deannise; Jimenez, Keith Lee; Naparan, Genesis (Journal of Management and Business Education, 2024)
This study examines the experiences of accounting interns during their On-the-Job Training (OJT) program in accounting firms, banking institutions, and government agencies. The research participants, who graduated from the accountancy program in 2022-2023, have completed the OJT program and are currently employed. Using the cognitive apprenticeship theory, the researchers explored the experiences of interns in their PJT. During their OJT, the accounting interns experienced immersive training, practical application, and interactions with colleagues. The on-the-job training experiences of the Accounting Interns contribute to their overall professional development and personal growth through building professionalism, developing workplace skills, employing adaptive resilience, and cultivating reflective learning. The OJT experiences prepare the Accounting Interns for their current job because they have developed positive workplace behaviour and efficiency. The challenges encountered by the Accounting Interns during OJT are unrelated or unfamiliar tasks, problems with social skills, difficulty in task organization, and difficulty adjusting to work culture and protocols. Accounting Interns cope with the challenges during their OJT through self-initiated learning, seeking help from colleagues, building confidence, time management, and observing professionalism. Furthermore, the OJT program combined academic knowledge with practical skills to improve students' career readiness. The experience prepared them for professional challenges in their fields. The findings of this study contribute to the exploration of the accountancy students during their OJT. Moreover, other students can find ways on how to deal with encountered problems as they undergo the OJT program.